Fatigue assessment for back-support exoskeletons during repetitive lifting tasks - Xiang, Xiaohan; Tanaka, Masahiro; Umeno, Satoru; Kikuchi, Yutaka; Kobayashi, Yoshihiko (Frontiers in Bioengineering and Biotechnology, 2024)
Fatigue is a major cause of low back pain for workers in various fields, including industry and agriculture. It has a negative impact on workers' safety, decreases their productivity, and causes a reduction in their occupational career. An exoskeleton is expected to be a solution for reducing workers' fatigue. However, assessing the safety and effectiveness of exoskeletons, except for the direct measurement of electromyography (EMG) in the human body, is challenging in real-case scenarios. Recently, simulations have been widely used to estimate biomechanical variables. Thus, we aimed to develop a method that combines an exoskeleton model and human body simulation to evaluate the effects of exoskeletons on lumbar fatigue. The strength and tendency estimated using this method are similar to those obtained from EMG devices in symmetrical repetitive lifting tasks. In addition, this method can be used to predict and simulate fatigue after a recorded motion. Our findings will help guide manufacturers in designing their products.